Characteristics of adherent and non-adherent patients with hypertension in a Norwegian cross-sectional study - Eirik Olsen; Lene V. Halvorsen; Stine Rognstad; Arleen Aune; Karl Marius Brobak; Ola Undrum Bergland; Vibeke N. Kjær; Knut Liestøl; Marit D. Solbu; Rune Mo; Eva Gerdts; Morten Rostrup; et al. (Exploration of Medicine)
Aim: Non-adherence is an important cause of uncontrolled hypertension. We investigated the prevalence of non-adherence to antihypertensive medications by serum drug concentration measurements in a cohort of Norwegian patients from the general population treated for hypertension. We also identified characteristics associated with non-adherence. Methods: Patients with hypertension using ≥ 2 antihypertensive agents were invited to participate in this national study performed in a semi-blinded fashion. Exclusion criteria were dementia, substance or alcohol abuse, pregnancy, terminal illnesses, poor Norwegian language skills, or severe kidney failure [glomerular filtration rate (GFR) < 30 mL/min/1.73 m2]. All patients had their antihypertensive drugs in serum analyzed by ultra-high-pressure liquid chromatography-tandem mass spectrometry to identify their adherence to the 23 most used antihypertensive agents. Additionally, they underwent a thorough standardized interview, office blood pressure (BP), and 24-hour ambulatory BP measurement. Results: n = 1,151 patients were investigated for BP control and drug adherence. Among these, n = 79 (6.9%) patients were identified as non-adherent, and n = 1,072 (93.1%) patients were identified as adherent by pharmacologists who reviewed the drug concentrations in blood in relation to self-reported prescribed medications. We found the non-adherent patients to be younger (56.9 vs. 63.7 years, p < 0.001), with higher systolic and diastolic office BP (150.4/91.4 vs. 143.2/82.0 mmHg, p < 0.01) and less likely to be of European ethnicity (82.9% vs. 95.8%, p < 0.001). Factors associated with non-adherence in logistic regression analysis were age, number of antihypertensive pills, non-European ethnicity, and inversely the use of angiotensin receptor blockers. Conclusions: We found fewer non-adherent patients than expected in patients on ≥ 2 antihypertensive drugs compared to previous investigations of patients on ≥ 3 antihypertensive drugs. We believe that selection at inclusion or possibly a higher confidence in physicians’ authority may be of importance. Adherence was significantly and negatively related to younger age, non-European ethnicity, and increasing number of prescribed antihypertensive pills, and positively to the type of prescribed medication, especially angiotensin receptor blocker (www.ClinicalTrials.gov identifier: NCT03209154).